2006
DOI: 10.1016/j.stam.2005.12.009
|View full text |Cite
|
Sign up to set email alerts
|

SPR sensor signal amplification based on dye-doped polymer particles

Abstract: A novel amplification method was prepared based on dye-doped polymer particles for SPR signals originating from antigen-antibody (BSAanti-BSA) interactions. Coloring the particles enhances the change of SPR signals based on the change of the imaginary part of the refractive index. The signal amplification effect in the reflectance mode was 31-fold stronger compared to the effect obtained with white latex particles and the combined amplification effect due to the presence of polymer particles and the colorant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Although gold nanoparticles (AuNPs) or nanorods are typically used in nanoparticle-enhanced SPRI, larger non-metallic nanoparticles can produce a comparable SPRI response that is independent of the distance from the gold thin film surface. 2325 To quantitatively measure the SiNP enhancement, a series of SPRI experiments were performed to examine the adsorption of ssDNA-modified SiNPs onto partially complementary mixed monolayer DNA microarrays. These two component SPRI measurements are in a similar form as studied previously.…”
Section: Resultsmentioning
confidence: 99%
“…Although gold nanoparticles (AuNPs) or nanorods are typically used in nanoparticle-enhanced SPRI, larger non-metallic nanoparticles can produce a comparable SPRI response that is independent of the distance from the gold thin film surface. 2325 To quantitatively measure the SiNP enhancement, a series of SPRI experiments were performed to examine the adsorption of ssDNA-modified SiNPs onto partially complementary mixed monolayer DNA microarrays. These two component SPRI measurements are in a similar form as studied previously.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the dielectric medium has a refractive index variation around its absorption band. The angular interrogation technique has been used to study the effect of dye doped polymer particles [9] or to investigate the sensing of ion-selective membranes [10]. These previous studies have shown an increase in the minimum of reflectivity as a function of the dye concentration, as well as a resonance angular shift.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these obstacles, we employed a sandwich-amplification strategy using NanoEnhancers that allowed us to detect CRP (model biomarker) in human serum at a LOD of 43 attomolar (5 fg/mL). Many previously reported strategies utilize gold nanoparticles in complex samples111227 or buffered conditions182829 to amplify the SPR signal for detection of biomolecules; however, the level of sensitivity attained with our platform is by far superior. Previously, we reported the use of NIR QDs for signal amplification of prostate specific antigen (PSA) using antibodies as capture probes and PEG-COOH/PEG-OH as the surface coating and attained a LOD of 2.5 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmonic field effects are known to improve the emission from fluorescent probes by several fold to produce highly directional and polarized emissions 17 . Moreover, the refractive index near the plasmonic surface is modified because of the presence of the fluorescent probes, thus affecting the excitation and propagation of the plasmon wave 18 19 . Recently, we have reported that the integration of near-infrared (NIR) QDs with SPRi enhanced the limit of detection (LOD, pg/mL) 15 due to a mass loading effect and spontaneous emission coupling with propagating surface plasmons.…”
mentioning
confidence: 99%